Symptom and comorbidity burden in hypertensive patients with obstructive sleep apnea - Tao, MengShi; Dong, Xiaoqi; Tu, Jinjing; Fang, Qing; Shao, Chuan (Frontiers in Endocrinology, 2024)
Background Obstructive sleep apnea (OSA) is an important but frequently overlooked risk factor for hypertension (HTN). The prevalence of hypertension is high in patients with OSA, but the differences in clinical symptoms and comorbidities between patients with OSA with hypertension and those with normal blood pressure have not been fully defined.This study retrospectively analyzed OSA patients diagnosed for the first time in Lihuili Hospital Affiliated to Ningbo University from 2016 to 2020. Patients were divided into an OSA group with hypertension and an OSA group without hypertension. The sociodemographic information, clinical symptoms, comorbidities, and polysomnography results of the two groups were compared. The independent risk factors associated with hypertension in patients with OSA were explored.Results A total of 1108 patients with OSA initially diagnosed were included in the study, including 387 with hypertension and 721 without. Compared with OSA patients without hypertension, OSA patients with hypertension were older; had a higher body mass index (BMI) and Epworth sleepiness score (ESS); a higher incidence of nocturia; and a higher proportion of diabetes mellitus, coronary heart disease, and cerebrovascular disease. Multivariate analysis showed age (odds ratio [OR]:1.06, 95% confidence interval [